Operationalizing One Health Employing Social-Ecological Systems Theory: Lessons From the Greater Mekong Sub-region - Wilcox, Bruce A.; Aguirre, A. Alonso; De Paula, Nicole; Siriaroonrat, Boripat; Echaubard, Pierre (Frontiers in Public Health, 2019)
The idea of the interdependency of the health of humans, animals and ecosystems emerged from the interplay of theory and concepts from medicine, public health and ecology involving leading thinkers in these fields during the last century. This idea has become the underlying tenet of the One Health perspective. Along with this tenet, the accruing dramatic pandemic threats arising from commensal wildlife microbes underlies One Health’s “human-animal-ecosystem interface” research focus imperative. Despite nearly a decade since the introduction of One Health its implementation has been limited. Herein we describe the impediments and solutions we have found while participating in numerous “One Health” projects. Efforts that ostensibly subscribe to this tenet and that focus inescapably require a willingness to go beyond one’s disciplinary training, understand and employ methods and procedures aligned with the socioecological systems and resilience framework. In this paper we briefly describe principles underlying the ecosystem approach to One Health, focusing particularly on the challenges of operationalizing transdisciplinary problem orientation, system thinking and participatory processes; and then discuss ecosystem approaches applied to One Health on how to bridge the epistemological, conceptual and methodological reductionist-holistic gap undermining the implementation of more integrative evidence–based approaches to the UN Sustainable Development Goals.